AGA704: Controlled Environment Crop Production / Faculty of Plantation and Agrotechnology - UiTM, Faculty of Plantation and Agrotechnology (Universiti Teknologi MARA (UiTM), 2018)
This course discusses controlled environment crop production as the effective technique to maximize yield and to produce high quality products with limited amount of resources and minimal impact to the environment. Major environmental factors affecting plant growth and development like lighting, gas supply, nutrient supply, temperature and humidity, can be strictly controlled by automated system under such crop production system. Knowledge on the interactions between plants and their microenvironments will be used to maximize harvest index. Lectures will also cover critical controlled environment issues and practices of plant production in greenhouses and growth chambers.